Health education role in promoting mothers’ beliefs, knowledge and practice of exclusive breastfeeding among King Fahd Armed Forces Hospital population - Shalaby, Hanin A.; Obaid, Rawan A.; Alharthi, Ruaa H.; Barayan, Malak M.; Bagabas, Noura S.; Battarjee, Raghdh M.; Baroom, Noura A.; Tallab, Mie A. (International Journal Of Community Medicine And Public Health, 2019)
Background: Breastfeeding is considered an optimal feeding method, as it fulfills the infants’ nutritional needs. Exclusive breastfeeding (EBF), which means to feed an infant solely (with some exceptions) on breast milk, is important for the health and well-being of both infant and mother. However, implementing an effective health education program is essential for promoting EBF and improving health awareness. Therefore, the purpose of this study is to measure mothers’ beliefs, knowledge and practice of exclusive breastfeeding before and after implementing the breastfeeding health education program at King Fahd Armed Forces Hospital (KFAFH). Methods: This study employs a quantitative research method and uses a cross-sectional study design. All in-patient and out-patient postnatal women who received information about EBF in their third trimester were evaluated post-delivery. In the period from December 2018 to March 2019, the total number of participants is (n=234). Results: The study indicates a statistically significant positive association between EBF knowledge and practice evaluation scores. Higher levels of breastfeeding (BF) knowledge were found to translate into better BF practice. Knowledge scores also had a significant association with beliefs, with higher knowledge being linked to more positive beliefs in relation to BF. Conclusions: The conducted study reports the major effect of health education intervention on EBF practice among the KFAFH population. As a result, some managerial, and clinical recommendations were addressed. Other recommendations focused on working mothers, as KFAFH may employ some strategies and polices to maximize the use of EBF.